2011
DOI: 10.1530/eje-11-0375
|View full text |Cite
|
Sign up to set email alerts
|

Plasma omentin-1 levels are reduced in non-obese women with normal glucose tolerance and polycystic ovary syndrome

Abstract: Objective: Omentin-1 is a novel adipokine that increases insulin sensitivity and is expressed in visceral adipose tissue. The aim of this study was to determine the metabolic parameters that influence plasma omentin-1 levels in women with polycystic ovary syndrome (PCOS). Design and methods: A cross-sectional study was performed in 87 women with PCOS and 53 body mass index (BMI)-matched healthy controls including 39 non-obese, normal-weight (NW) PCOS women with normal glucose tolerance (NGT) and 44 BMI-and hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 29 publications
1
37
2
Order By: Relevance
“…The correlation between HDL cholesterol and omentin-1 has been previously described in the settings of obesity, metabolic syndrome, diabetes, and cardiovascular disease [4,8,10,12,13,17,26]. However, unlike other studies, we found that the association was primarily in men and in the presence of the metabolic syndrome.…”
Section: Discussioncontrasting
confidence: 59%
“…The correlation between HDL cholesterol and omentin-1 has been previously described in the settings of obesity, metabolic syndrome, diabetes, and cardiovascular disease [4,8,10,12,13,17,26]. However, unlike other studies, we found that the association was primarily in men and in the presence of the metabolic syndrome.…”
Section: Discussioncontrasting
confidence: 59%
“…The same conclusion can be made in regard of omentin IHC studies advisability, since—as had been discovered by us—a connection between this adipokine mRNA expression in omental fat and clinical-morphological EC features was rather modest (Table 4). Of note, in EC patients’ population we could not find any association between serum omentin concentration or its mRNA expression in omental tissue samples and BMI value (data not presented) in spite of published evidence of negative correlation between serum omentin level and excessive body mass (Tan et al 2008) [although there is also a report stating the contrary (Choi et al 2011)]. One also should not forget that while omentin is commonly viewed as a typical visceral adipokine, it (as already mentioned in Introduction) is mostly produced by fat tissue stromal cells but not adipocytes (Yang et al 2006).…”
Section: Discussionmentioning
confidence: 70%
“…In the setting of PCOS, plasma omentin-1 concentrations were found to decrease in non-obese women with normal glucose tolerance and PCOS and overweight insulin-resistant women with PCOS when compared with control subjects (Table 1; Tan et al 2008a, Choi et al 2011. In addition, the expression of omentin-1 at both mRNA and protein levels in omental adipose tissue is decreased in non-obese women with PCOS compared with controls (Tan et al 2008a).…”
Section: Omentin-1mentioning
confidence: 98%